2015
DOI: 10.1021/cs501698w
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Comparison of Methanol Decomposition and Reverse Reactions on Metal Surfaces

Abstract: Methanol decomposition on metals has been subject of several theoretical studies, usually concentrating on a particular set of reactions in the main reaction path. In this work, we present an extensive study that considers all potential elementary steps for four close-packed surfaces including Cu, Ru, Pt, and Pd that shows the different behaviors and alternative routes through which the decomposition can take place by theoretical methods, including dispersion contributions. Decomposition follows different path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
121
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(137 citation statements)
references
References 66 publications
(133 reference statements)
6
121
1
Order By: Relevance
“…For the methanol decomposition, the initial C−O bond scission is too hard to occur in general, while the O−H or C−H bond scission is favorable in different cases. For example, it proceeds preferably through the initial O−H bond scission on Ru(0001), 57 Cu(111), 57,77 and PtZn(111), 46 but the C−H bond scission is favorable on Pt(111) 54,57 and Pd(111). 57,69 To confirm the reaction network, we describe all the possible elementary steps in the methanol decomposition via both the initial O−H and C−H bond scissions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the methanol decomposition, the initial C−O bond scission is too hard to occur in general, while the O−H or C−H bond scission is favorable in different cases. For example, it proceeds preferably through the initial O−H bond scission on Ru(0001), 57 Cu(111), 57,77 and PtZn(111), 46 but the C−H bond scission is favorable on Pt(111) 54,57 and Pd(111). 57,69 To confirm the reaction network, we describe all the possible elementary steps in the methanol decomposition via both the initial O−H and C−H bond scissions.…”
Section: Resultsmentioning
confidence: 99%
“…45,58 Generally, the Pt(111) surface is the most stable crystal plane in Pt nanoparticles and thus is usually selected as the prototype in both experimental and theoretical investigations. 36,37,43,53,54,57 For comparison, the PtRu(111) surface was considered here. Furthermore, the PtRu(111) surface was computed with the fcc structure, which is the experimentally observed structure.…”
Section: Model and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Starting from this early proposal, several alternative formulations that end up correlating with a single adsorption energy have been derived. [18][19][20][21][22][23] In particular, the transition state scaling (TSS) relationships correlate the transition state energy with the energy of the initial or the final state of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…García-Muelas et al [13] investigated methanol decomposition on metals, including Cu, Ru, Pt and Pd, and found that decomposition follows different paths on these metals. On Ru(0001) surface, methanol decomposition initially begins from O-H bond cleavage to produce methoxy species that subsequently dehydrogenate to CO and hydrogen with no significant C-O bond breakage.…”
Section: Introductionmentioning
confidence: 99%